Singing Activities to Develop Well-being of Students in State Primary School X, Tegal Bedug, Lelea, Indramayu, West Java - Dariyo, Agoes (Universitas Negeri Surabaya, 2025)
Student Well-being is the psychological well-being felt by a student while carrying out their duties and responsibilities as a student who masters the scientific field taught by teachers at school. Every student is expected to have a psycho-emotional condition that motivates him to really study diligently and be able to show the best academic achievement. Student well-being can be developed through activities that are interesting, fun, and happy for each individual, such as singing. This research activity involved elementary school students (N=32). This activity uses an experimental approach, which includes 3 stages, namely pre-activity, activity, and post-activity stages. The data collection technique uses a student well-being questionnaire and is given during the pre-test and post-test. The data analysis technique uses a difference test (t-test), namely, differentiating the results of the pre-test and post-test. The results of the activity show that singing activities can develop student well-being in elementary school students.